Synthetic polypeptides using a biologic as a reference medicinal product – the European landscape of regulatory approvals - Klein, Kevin; Heisterberg, Jens; Stolk, Pieter (Frontiers in Medicine, 2024)
Recent advances in synthetic drug manufacturing have introduced a new dynamic to the European regulatory system, with chemically synthesized polypeptide products using biological originator products as their reference medicine. Whereas biosimilars are subject to a dedicated regulatory framework in the EU, synthetically produced follow-on products are not eligible for assessment through this pathway, requiring approval via the traditional generic pathway under Article 10(1), or via the hybrid pathway under Article 10(3). This review presents an overview of recent developments in the field of synthetic peptides referencing biological originators in the EU. The use of different regulatory procedures can have potential implications for regulatory assessments, clinical practice and pharmacovigilance. As more complex synthetic products referencing recombinant originator products are expected in the coming years, this study promotes more transparency as well as global alignment about regulatory procedures for chemically synthesised products referencing biological originator products to ensure approval of safe and high-quality generics.